COMBINED IMPACT OF EMBEDDEDNESS KNOWLEDGE AND SPECIFIC KNOWLEDGE IN REDUCING STRATEGIC DRIFT - Sanaa J. Kadhim; Suhad Khaled Halil (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The present study aims to reveal the combined impact of embodied knowledge and the specific knowledge of (contextual and technological specific knowledge) in addressing strategic drift in its dimensions (poor communication, weak strategic flexibility, and deteriorating performance), as the study attempts to address a realistic problem reflected in the backfilling of strategic drift among management leaders in universities and colleges in central and southern middle Euphrates through embodied knowledge and specific knowledge, the researcher distributed (175) Questionnaire form randomly, the number of forms valid for analysis (153) or 87.4% response rate, analyzed using advanced statistical software (SPSS.V.27 & AMOS.V.26), the current study is a pioneer in its variables, as it addresses important variables that will highlight how strategic drift is addressed through embodied knowledge and specific knowledge, The study summarized a set of conclusions, most notably the existence of a moral common influence relationship of the knowledge embodied and knowledge defined in the strategic drift of its dimensions. This means that strategic drift can be addressed through the investment of embodied knowledge and knowledge specific to both types of contextual defined knowledge. Specific technological knowledge to improve management leaders' skills and expertise in colleges studied in order to develop and formulate appropriate strategies to address poor communication, weak strategic flexibility, and deteriorating performance.